Hsa-miR-520d induces hepatoma cells to form normal liver tissues via a stemness-mediated process - Tsuno, Satoshi (Nature Publishing Group, 2014)
The human ncRNA gene RGM249 regulates the extent of differentiation of cancer cells and the conversion of 293FT cells to hiPSCs. To identify the factors underlying this process, we investigated the effects of lentivirally inducing miR-520d expression in 293FT and HLF cells in vitro. Subsequently, we evaluated tumor formation in a xenograft model. Transformed HLF cells were Oct4 and Nanog positive within 24 h, showed p53 upregulation and hTERT downregulation, and mostly lost their migration abilities. After lentiviral infection, the cells were intraperitoneally injected into mice, resulting in benign teratomas (6%), the absence of tumors (87%) or differentiation into benign liver tissues (7%) at the injection site after 1 month. We are the first to demonstrate the loss of malignant properties in cancer cells in vivo through the expression of a single microRNA (miRNA). This miRNA successfully converted 293FT and hepatoma cells to hiPSC-like cells. The regulation of malignancy by miR-520d appears to be through the conversion of cancer cells to normal stem cells, maintaining p53 upregulation.